PAX3-FOXO1 escapes miR-495 regulation during muscle differentiation. Issue 1 (2nd January 2019) - Xie, Zhongqiu; Tang, Yue; Su, Xiaohu; Cao, Junwei; Zhang, Yanru; Li, Hui
ABSTRACT: Pax3 plays an essential role in myogenesis. Previously, we found a tumor-signature chimeric fusion RNA, PAX3-FOXO1 also present during muscle differentiation, raising the possibility of its physiological role. Here we demonstrated that the fusion is needed transiently for muscle lineage commitment. Interestingly, the fusion ortholog was not found in seven mouse muscle differentiation/regeneration systems, nor in other stem cell differentiation systems of another three mammal species. We noticed that Pax3 is expressed at a much lower level in human stem cells, and during muscle differentiation than in other mammals. Given the fact that the fusion and the parental Pax3 share common downstream targets, we reasoned that forming the fusion may be a mechanism for human cells to escape certain microRNA regulation on Pax3 . By sequence comparison, we identified 16 candidate microRNAs that may specifically target the human PAX3 3ʹUTR. We used a luciferase reporter assay, examined the microRNAs expression, and conducted mutagenesis on the reporters, as well as a CRISPR/Cas9 mediated editing on the endogenous allele. Finally, we identified miR-495 as a microRNA that specifically targets human PAX3 . Examining several other fusion RNAs revealed that the human-specificity is not limited to PAX3-FOXO1 . Based on these observations, we conclude that PAX3-FOXO1 fusion RNA is absent in mouse, or other mammals we tested, the fusion RNA is a mechanism to escape microRNA, miR-495 regulation in humans, and that it is not the only human-specific fusion RNA.